2021
DOI: 10.1002/qre.3036
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of coefficient of variation with function‐based adaptive exponentially weighted moving average control chart

Abstract: In this paper, a new adaptive control chart is presented to study the relative process variability, which is called the coefficient of variation (CV). The CV study is the monitoring of a process with an unstable mean value over time. So, a function-based adaptive exponentially weighted moving average (FAEWMA) CV control chart is proposed to detect the infrequent changes in the process CV, named as "FAEWMA CV" control chart. The function is suggested to adapt the smoothing constant (SC) of the plotting statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…For CV charts that do not fall in any of these categories, they are classified under the “others” category. The EWMA‐based CV charts were proposed by Hong et al., 2,3 Castagliola et al., 4 Zhang et al., 5 Yeong et al., 6 Muhammad et al., 7 Zhang et al., 8 Haq and Khoo, 9 Teoh et al., 10 Arshad et al., 11 and Hu et al 12 . CV charts that are based on the CUSUM approach were suggested by Lee et al., 13,14 Tran and Heuchenne, 15 Tran et al., 16 and Tran and Heuchenne 17 .…”
Section: Introductionmentioning
confidence: 99%
“…For CV charts that do not fall in any of these categories, they are classified under the “others” category. The EWMA‐based CV charts were proposed by Hong et al., 2,3 Castagliola et al., 4 Zhang et al., 5 Yeong et al., 6 Muhammad et al., 7 Zhang et al., 8 Haq and Khoo, 9 Teoh et al., 10 Arshad et al., 11 and Hu et al 12 . CV charts that are based on the CUSUM approach were suggested by Lee et al., 13,14 Tran and Heuchenne, 15 Tran et al., 16 and Tran and Heuchenne 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Tran and Heuchenne 28 presented CV control chart by using the variable sampling based CUSUM control chart. Arshad et al 29 suggested a function based CV control chart for monitoring the shifts in CV.…”
Section: Introductionmentioning
confidence: 99%